2001
DOI: 10.1016/s0005-2736(01)00409-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery and triggered release of liposomal doxorubicin enhances cytotoxicity against human B lymphoma cells

Abstract: Dioleoylphosphatidylethanolamine (DOPE)-containing liposomes that demonstrated pH-dependent release of their contents were stabilized in the bilayer form through the addition of a cleavable lipid derivative of polyethylene glycol (PEG) in which the PEG was attached to a lipid anchor via a disulfide linkage (mPEG-S-S-DSPE). Liposomes stabilized with either a non-cleavable PEG (mPEG-DSPE) or mPEG-S-S-DSPE retained an encapsulated dye at pH 5.5, but treatment at pH 5.5 of liposomes stabilized with mPEG-S-S-DSPE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(117 citation statements)
references
References 33 publications
3
113
0
Order By: Relevance
“…The appropriate addition of DOPE has been reported to increase the gene delivery efficiency of cationic liposomes. [49][50][51] In an effort to research the influence of cationic lipid/DOPE ratios on the capacity of gene delivery efficiency, we prepared a series of cationic liposomes with different cationic lipid/DOPE molar ratios of 1 : 0.5, 1 : 1, 1 : 2, and 1 : 3 at equal lipid/DNA molar ratio of 3 : 1. The transfection activity was evaluated through the percent of positive transfected cells and MFI by flow cytometry in 293T cells as shown in Fig.…”
Section: Synthesis Of the Cationic Lipids T-c12-ah And T-c16-ah The Cmentioning
confidence: 99%
“…The appropriate addition of DOPE has been reported to increase the gene delivery efficiency of cationic liposomes. [49][50][51] In an effort to research the influence of cationic lipid/DOPE ratios on the capacity of gene delivery efficiency, we prepared a series of cationic liposomes with different cationic lipid/DOPE molar ratios of 1 : 0.5, 1 : 1, 1 : 2, and 1 : 3 at equal lipid/DNA molar ratio of 3 : 1. The transfection activity was evaluated through the percent of positive transfected cells and MFI by flow cytometry in 293T cells as shown in Fig.…”
Section: Synthesis Of the Cationic Lipids T-c12-ah And T-c16-ah The Cmentioning
confidence: 99%
“…In another approach, DOPE-containing liposomes were stabilized in the bilayer form through the addition of a cleavable lipid derivative of PEG in which the polymer was attached to a lipid anchor via a disulfide linkage (PEGUSUSUDSPE) [56,57]. Liposomes stabilized with either a non-cleavable PEG (PEGUDSPE) or PEGUSUSUDSPE retained an encapsulated dye at pH 5.5.…”
Section: Long-circulating Dope-containing Ph-sensitive Liposomesmentioning
confidence: 99%
“…Pharmacokinetic studies suggested that PEGUSU SUDSPE was rapidly cleaved in circulation. In addition, therapeutic studies performed in a murine model of B-cell lymphoma demonstrated clearly that the developed pH-sensitive formulation targeted to the CD19 receptor was superior to stable, long-circulating, targeted non-pH-sensitive liposomes, despite the more rapid drug release and clearance of the pH-sensitive formulation [57].…”
Section: Long-circulating Dope-containing Ph-sensitive Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DOPE-containing liposomes can enhance drug delivery to cells, in vivo results were less than desired, because these liposomes had very short circulation times despite the addition of PEG onto the surface of liposomes [146]. Recently, DOPE-free liposomes targeted via transferrin and containing a fusogenic peptide (GALA) incorporated on the liposome surface have been shown to fuse efficiently with the endosomal membrane after internalization [147]; because it is known that surface PEG can interfere with liposome fusion [148], these GALA-modified liposomes were classical liposomes that lacked a stabilizing polymer such as PEG on the liposome surface.…”
Section: Triggered Release Systemsmentioning
confidence: 99%